Resorcinol-formaldehyde (RF) as a novel plasticizer for starch-based solid biopolymer electrolyte - Selvanathan V.; Ruslan M.H.; Aminuzzaman M.; Muhammad G.; Amin N.; Sopian K.; Akhtaruzzaman M. (MDPI AG, 2023)
Biodegradable polymers; Biopolymers; Crosslinking; Crystallinity; Formaldehyde; Fourier transform infrared spectroscopy; Lithium; Phenols; Plasticizers; Reinforced plastics; Solid electrolytes; Starch; Amorphous regions; Biopolymer electrolyte; FT-IR spectrum; Lithium triflate; Polymer electrolyte membranes; Resorcinol formaldehydes; Room-temperature conductivity; Solution-casting technique; Polyelectrolytes